FAKTOR DAN KONDISI YANG MEMPENGARUHI PERKEMBANGAN SOSIAL EMOSIONAL AUD DI MASA COVID 19 - fakhrana, ayu; nasution, candri wulan; khadijah, khadijah (Kumarottama: Jurnal Pendidikan Anak Usia Dini, 2022)
This research was carried out in the Percut Sei Tuan sub-district community in Laut Dendang Village, where researchers saw, reviewed and observed based on several respondents from parents, teachers and the community. about the factors and conditions that affect the social and emotional development of children during this COVID-19 period. This study aims to determine: (1) the relationship of social emotional development in early childhood (2) the factors that influence the social emotional development of children (3) the conditions that affect the social emotional development of children in the Percut Sei Tuan sub-district community in Laut Dendang village. This type of research is descriptive research. The research approach used is case study approach that is literature study (library search). Sources of data/subjects in this study were several respondents who were interviewed and observed. Qualitative research is to understand the phenomenon of what is experienced And the method of collecting secondary data is obtained from published data.